APPROACHES TO THE TEACHING OF SPEAKING - Kholkhodjaevich, Zafar (Журнал иностранных языков и лингвистики, 2023)
Current literature (Hedge (2004), Schmitt (2002), Richards (1994), Dornyei and Thurrell 1994) indicates that, at present, there are two chief approaches to the teaching of speaking – Indirect and Direct.